A case of squamous cell carcinoma arising in a giant porokeratosis previously diagnosed as psoriasis - Lorry Aitkens; Joel Byrne; Charay Jennings-Dover; Kathryn Anne Potter (PAGEPress Publications, 2022)
Porokeratosis (PK) is a disorder of keratinization with a clinical presentation of an atrophic center surrounded by a hyperkeratotic border. Lesions of porokeratosis carry a risk of malignant transformation with giant porokeratosis (GPK) being a high-risk variant. We report a case in which a single, large, erythematous, scaly plaque in an immunocompromised patient showed initial histopathological features consistent with psoriasis and subsequent histological features consistent with GPK. This plaque underwent malignant transformation to SCC on three occasions. This case highlights that specimens taken from central portions of porokeratosis may resemble a variety of dermatoses histologically, including psoriasis, resulting in misdiagnosis as seen in our patient. When a patient presents with a diagnosis previously made that isn't responding to therapy as expected, repeat biopsy is appropriate.